2004
DOI: 10.1590/s0073-47212004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo biológico de Simpulopsis ovata (Gastropoda, Bulimulidae) em São Francisco de Paula, Rio Grande do Sul, Brasil

Abstract: ABSTRACT. Biological cycle of Simpulopsis ovata (Gastropoda, Bulimulidae) in São Francisco de Paula, Rio Grande do Sul, Brazil. The population growth of Simpulopsis ovata (Sowerby, 1822) from the Centro de Pesquisas e Conservação da Natureza -Pró-Mata, São Francisco de Paula, Rio Grande do Sul, Brazil, was studied along eleven months of 1996. Two discontinuous age classes were identified. The first one, with a monthly growth rate of 1.55 mm, was reproductively mature during April and May. The second one appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…When compared to other invasive species, growth rates were similar, as C. fluminea (Müller, 1774) that had K = 0.65, L ∞ = 32 mm and t 0 = 0.5 (Cataldo & Boltovskoy, 1999). Gomes, Silva, Gil, & Thomé, 2004 In relation birth size, according to Dudgeon (1986) M. tuberculata born with 2.2-3.4 mm. In opposition, the present study showed a higher value, being the size at birth of 5.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to other invasive species, growth rates were similar, as C. fluminea (Müller, 1774) that had K = 0.65, L ∞ = 32 mm and t 0 = 0.5 (Cataldo & Boltovskoy, 1999). Gomes, Silva, Gil, & Thomé, 2004 In relation birth size, according to Dudgeon (1986) M. tuberculata born with 2.2-3.4 mm. In opposition, the present study showed a higher value, being the size at birth of 5.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in the results, the growth curve of A. fulica follows this pattern, with a rapid growth until two years old (> 90 mm) becoming slower as the animal becomes older. Gomes et al (2004), in studies with land pulmonates gastropods in Rio Grande do Sul, came to the conclusion that the cycle of life of population of Simpulopsis ovata (Sowerby, 1822) is annual and the species is semelparous (the species has only one reproductive event, that is, adult individuals die after the reproductive period), also, affirm that annual cycles have been commonly found among land pulmonate gastropods as Helicella (Xerothracia) pappi (Schü tt, 1962), Salinator takii Kuroda, 1928) (Lazaridou-Dimitriadou 1995, Kosuge 2000. Unlike these land pulmonates with short life cycle, A. fulica can live, in the wild life, more than four years and reproduce from 15 to 25 times in its life, this fact, combined to series of other makes the species an excellent invader.…”
Section: Aspects Of Population Dynamics Of Achatina Fulicamentioning
confidence: 99%
“…Distinguem-se das espécies aqui propostas, quanto à anatomia: S. miersi (Pfeiffer, 1856), por suas fileiras transversais radulares dispostas em " V", dentes centrais unicúspides com mesocono ovalado (ARAÚ JO & BREURE, 1977); S. ovata, por apresentar distinto padrão de coloração do manto constituído por manchas negras (ARAÚ JO, 1975;GOMES et al, 2004); S. pseudosulculosa Breure, 1975, cuja glândula gametolítica é triangularalongada (BREURE, 1975); S. sulculosa (Férussac, 1821), por ter uma glândula gametolítica globosa e curta, glândula do albume alongada e apresentar dois músculos retratores do falo (BREURE, 1975); S. wiebesi Breure, 1975, por seu evertofalo ondulado e inserção distal do músculo retrator do falo no flagelo (BREURE, 1975) e pelos dentes centrais radulares com mesocono lanceolado, cujos ectoconos são pequenos e destacados do mesocono .…”
Section: Mínunclassified